PENGARUH CORPORATE GOVERNANCE TERHADAP CASH HOLDING PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Mawardi Mawardi; Nurhalis Nurhalis (Jurnal Manajemen Inovasi, 2018)
This study aimed to examine the effect of Corporate Governance on Cash Holding. The Independent variables in this research are the insider ownership, board independent and institutional ownership, for the dependent variable is cash holding that proxied by Ln kas setara kas. This study use data of 37 companies manufacture in the Indonesian Stock Exchange for the periode 2010 until 2014. The sampling method used in this study was purposive sampling, is sampling based criteria. The analysis technique used in this study using multiple regression analysis with using program SPSS 21. The result showed that:1(1)insider ownership have negative effect on cash holding, (2) board independent have positive effect on cash holding, (3) institutional ownership have negative effect on cash holding. The results of this study are expected to be taken into consideration for the company in decision making related to the implementation of good corporate governance on firm so as to minimize conflicts of interest within the company Keywords: Independent Commissioner,Managerial Ownership,Institutional Ownership CashHolding.